Greek ostraka in the British Library - Toth, P (Centro di Studi Papirologici dell’Università del Salento, 2021)
The British Library holds one of the largest collections of Greek ostraka outside Egypt. The paper presents the history of the collection from its beginnings in the early 19th century up to its present status, surveying the various attempts to catalogue it from early facsimiles to digitized images. It highlights the crucial importance of cross-institutional collaboration for future research on the collection with examples of successful projects.